INTELLIGENT MANUFACTURING SYSTEMS AND DIGITAL TWINS (Uzbekistan Open Conference, 2025)
This article examines the concepts of Intelligent Manufacturing Systems (IMS) and Digital Twins (DT) as key drivers of the Industry 4.0 paradigm. Their role in enhancing the efficiency, flexibility, and sustainability of industrial processes is analyzed. Special attention is given to the integration of these technologies to create self-optimizing production environments capable of predicting failures, modeling "what-if" scenarios, and making autonomous decisions.